1999
DOI: 10.1523/jneurosci.19-13-05506.1999
|View full text |Cite
|
Sign up to set email alerts
|

Brain Mechanisms of Propofol-Induced Loss of Consciousness in Humans: a Positron Emission Tomographic Study

Abstract: In the present study, we used positron emission tomography to investigate changes in regional cerebral blood flow (rCBF) during a general anesthetic infusion set to produce a gradual transition from the awake state to unconsciousness. Five right-handed human volunteers participated in the study. They were given propofol with a computer-controlled infusion pump to achieve three stable levels of plasma concentrations corresponding to mild sedation, deep sedation, and unconsciousness, the latter defined as unresp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
221
1
6

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 408 publications
(255 citation statements)
references
References 59 publications
21
221
1
6
Order By: Relevance
“…However, this study and also several other studies in anaesthesia or in the vegetative state (Fiset et al, 1999;Alkire et al, 2000;Laureys et al, 2000) showed that significantly greater reduction was seen in multiple regions of the prefrontal cortex, the superior frontal gyrus, the anterior cingulate gyrus, the parietal association areas, the insula and the thalamus. The majority of these areas constitute the DMRSN or have a close relationship to it.…”
Section: Discussionsupporting
confidence: 64%
“…However, this study and also several other studies in anaesthesia or in the vegetative state (Fiset et al, 1999;Alkire et al, 2000;Laureys et al, 2000) showed that significantly greater reduction was seen in multiple regions of the prefrontal cortex, the superior frontal gyrus, the anterior cingulate gyrus, the parietal association areas, the insula and the thalamus. The majority of these areas constitute the DMRSN or have a close relationship to it.…”
Section: Discussionsupporting
confidence: 64%
“…These include the thalamus and PCC/PrCC (Fiset et al, 1999;Kaisti et al, 2002). Although individual changes in rCBF did not correlate with propofol concentrations and the differences between three levels of propofol were not significant for any areas (Kaisti et al, 2002), this latter study did show that the lowest concentration of propofol assessed produced a profound average reduction in PCC/PrCC and Fiset et al, (1999) showed a strong negative correlation between rCBF in the thalamus and PCC/PrCC and propofol concentration. Furthermore, the close correlation of activity under propofol in the thalamus and midbrain in this latter study confirms the relevance of the reticular projections to thalamus as mediating arousal and initiation of consciousness.…”
Section: Anesthetic Sensitivitymentioning
confidence: 49%
“…In the present study, we showed that in 5 of 10 subjects, the signals of thalamus were decreased during propofol anesthesia although the changes were weak and significantly different compared with the changes in hypothalamus, frontal lobe, and temporal lobe. However, most of the studies using PET reported that the thalamus was important in anesthesia (Fiset et al, 1999). We think that the probable reasons for these different results are the imaging methods and the doses of propofol used.…”
Section: Discussionmentioning
confidence: 97%